METHODS FOR COMPLEX EVALUATION OF THE QUALITY LEVELOF AGRICULTURAL PRODUCTS (BY THE EXAMPLE OF WHEAT GRAIN) - Shurshikova G.V.; Kotarev V.I.; Derkanosova N.M.; Vasilenko O.A.; Zolotareva N.I. (Техника и технология пищевых производств)
The product quality depends on the level of functional and technological characteristics of agricultural raw materials as determined inrelation to the laws of formation of consumer properties of certain foods. Current conditions of forming the consumer market determine the need for the rational use of the potential of domestic raw material sources. The purpose of the research is to develop a comprehensive method for evaluating the quality level of agricultural products adapted by the example of functional and technological properties of wheat in relation to the provision of consumer properties of bakery products. The object of the study is wheat grain of class 3 (the Voronezh region). The mathematical tool of this method is the theory of fuzzy sets. Fuzzy classifier for grain property evaluation has been developed; the set of six indices that form the functional and technological properties of grain has been determined; the values of indices have been arranged and presented by linguistic variables with trapezoidal membership function; the rules for calculating the membership functions are given. Features for describing individual indices, for example, «the quality of raw gluten», have been considered. For the sample of wheat grain, the values of membership functions of linguistic variables «index level» for all indices and linguistic variable «quality level» have been calculated. It has been determined, that the studied sample of grain has the second (medium) quality level. Therefore, it can be recommended for the production of bread flour for special sorts, including long loaves, small loaves, flaky pastry, dietetic products, except gluten-free, flaky cookies and biscuits. Evaluation of the level of functional and technological properties of agricultural products enables to use raw materials for the production of foods for a certain segment of consumers (children, dietary and other special food), specific technologies (traditional, accelerated, etc.), and types of products and thereby to exploit efficiently the resource potential of agro-industrial complex.